1993
DOI: 10.1017/s0813483900005465
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning and Cognitive-Behaviour Therapy

Abstract: When behaviour therapy was developed in the 1950s and 1960s, it was based firmly on the experimental psychology of the time, principally learning theory. Since that time effective verbal therapies have been developed, and clinicians are faced with the difficult task of selecting among so-called behavioural and cognitive interventions based on radically different philosophies. This paper reviews developments in learning theory, particularly human learning, which suggest that conditioning is a complex cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 41 publications
4
16
0
Order By: Relevance
“…We accept and embrace this view. However, we do not accept the idea that a modern view of conditioning implies that conditioning trials inevitably give rise to a kind of prepositional, declarative knowledge that is the same as that created by verbal input (e.g., Lovibond, 1993). Conditioning theories themselves are agnostic on the issue.…”
Section: Clarifying the Role Of Classical Conditioning In Pdmentioning
confidence: 74%
“…We accept and embrace this view. However, we do not accept the idea that a modern view of conditioning implies that conditioning trials inevitably give rise to a kind of prepositional, declarative knowledge that is the same as that created by verbal input (e.g., Lovibond, 1993). Conditioning theories themselves are agnostic on the issue.…”
Section: Clarifying the Role Of Classical Conditioning In Pdmentioning
confidence: 74%
“…Second, we have discussed the reduction of a neophobic response as an instance of habituation of unconditioned fear. The idea that the same mechanisms that operate in the extinction of a conditioned fear might also be involved in the reduction of an unconditioned fear is not new (e.g., Lovibond, 1993;Reiss, 1991). However, from a strict point of view, extinction of any response requires previous conditioning and, thus, the reduction of an unconditioned fear might be viewed as a process resembling (but different from) extinction, that is, habituation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that not all fear responses arise from conditioning episodes (Rachman, 1977). Additionally, there are reasons to assume that the mechanisms operating in exposure therapy that are effective in extinguishing a previously conditioned fear also play an important role in the treatment of unconditioned fears (e.g., Lovibond, 1993;Reiss, 1991). If exposure to an unconditioned fear-eliciting stimulus results in habituation of the unconditioned fear owing to the same mechanisms that mediate extinction of a conditioned fear, one might expect the presence of a safety signal to also impair the habituation of an unconditioned fear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, exposure to interoceptive sensations (e.g., breathlessness, pounding heart) in panic disorder is used explicitly as a way of testing the patient's catastrophic interpretations (e.g., heart attack) and is linked to verbal information concerning the true causes of those sensations (e.g., hyperventilation, anxiety). Thus, direct experience and language can be seen as two different and potentially synergistic ways of targeting patients' distorted beliefs and thereby normalizing their behavior (Lovibond 1993). Further exploration of the ways in which learning experiences impact on propositional knowledge may well facilitate progress in developing effective clinical interventions.…”
Section: The Clinicmentioning
confidence: 99%